2010
DOI: 10.1016/j.yjmcc.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 and Stim1 regulate normal and hypertrophic growth in cardiomyocytes

Abstract: Cardiac hypertrophy is an independent risk for heart failure (HF) and sudden death. Deciphering signalling pathways dependent on extracellular calcium (Ca2+) influx that control normal and pathological cardiac growth may enable identification of novel therapeutic targets. The objective of the present study is to determine the role of the Ca2+ release-activated Ca2+ (CRAC) channel Orai1 and stromal interaction molecule 1 (Stim1) in postnatal cardiomycoyte store-operated Ca2+ entry (SOCE) and impact on normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(173 citation statements)
references
References 17 publications
16
153
2
2
Order By: Relevance
“…SOCE is therefore an attractive candidate to link the Ca 2+ and membrane clocks that underlie SANC automaticity. Roles for STIM1-dependent SOCE have been suggested in the heart (10)(11)(12)(13)(14). Here, we show that STIM1 is selectively expressed in the SAN where it activates Ca 2+ entry via Orai1 channels and thereby modulates the Ca 2+ signals required for pacemaking activity of the SAN.…”
mentioning
confidence: 60%
“…SOCE is therefore an attractive candidate to link the Ca 2+ and membrane clocks that underlie SANC automaticity. Roles for STIM1-dependent SOCE have been suggested in the heart (10)(11)(12)(13)(14). Here, we show that STIM1 is selectively expressed in the SAN where it activates Ca 2+ entry via Orai1 channels and thereby modulates the Ca 2+ signals required for pacemaking activity of the SAN.…”
mentioning
confidence: 60%
“…Previously, research in rodent models has demonstrated that SOCE, STIM1, and Orai1 play crucial roles in the development of cardiomyocyte hypertrophy [8][9][10], whereas NO, cGMP, and PKG exert antihypertrophic effect [6,11,34]. However, one of the challenges in exploring mechanistic insight of Orai1 and/or NO-cGMP-PKG effect is lack of human cardiomyocytes for research.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to their earlier study (78), they also found that TRPC1 expression was upregulated in response to ET-1; interestingly, this increase was also attenuated following knockdown of STIM1. Subsequently, Voelkers and colleagues showed that SOCE and hypertrophic signaling induced by PE treatment were reduced following knockdown of both STIM1 and Orai1 (130).…”
Section: Orai1/trpcmentioning
confidence: 99%